INOVASI PELAYANAN ADMINISTRASI KEPENDUDUKAN (ADMINDUK) MELALUI APLIKASI ADMINISTRASI KEPENDUDUKAN CEPAT AKURAT TERINTEGRASI (PANDU CAKTI) DI KANTOR DISPENDUKCAPIL KABUPATEN TULUNGAGUNG - Tsamara Dilla Zica; Eva Hany Fanida (Publika, 2022)
A good public service can be judged from how the service is carried out in accordance with the service standards that have been set. The Department of Population and Civil Registration of Tulungagung Regency has published an online-based application innovation called the Integrated Fast Accurate Population Administration (Pandu Cakti). This research was conducted at the Dispendukcapil Tulungagung Regency which aims to describe the innovation of integrated fast accurate administration services (Pandu Cakti). This study uses a descriptive method with a qualitative approach and uses an analytical knife of the supporting factors in the success of e-Government innovation based on Kalvet theory (2012). The data collection technique used observation, interviews and documentation and also the determination of the sources with snowball sampling and analyzed using data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the innovation of Pandu Cakti of the Department of Population and Civil Registration of Tulungagung Regency has fulfilled six supporting factors in the success of e-Government innovation based on Kalvet theory (2012). The leadership factor has been going well where the leader carries out his duties well and is able to create innovations to solve problems that have not been resolved so far. The funding factor, in which this innovation uses funds from the APBD and there are no obstacles in funding. Legislative and regulatory support factors have gone well with the written basis and SOP. The development factor of information technology infrastructure (strategic) has been going well even though there are several obstacles in the network. The partnership factor with the public sector, the existence of partnerships with the public sector, namely all Village Offices and District Offices in Tulungagung Regency. The competence factor of the private sector, there is competence in the field of making applications, namely in coding by third parties. Keyword: Public service, Service Innovation, Admin Service, Pandu Cakti